2023
DOI: 10.3892/etm.2023.12154
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure pulmonary edema (Review)

Abstract: Negative pressure pulmonary edema (NPPE) is a complication resulting from acute or chronic upper airway obstruction, often posing challenges in recognition and diagnosis for clinicians. If left untreated, NPPE can lead to hypoxemia, heart failure and even shock. Furthermore, the drug treatment of NPPE remains a subject of controversy. The primary pathophysiological mechanism of NPPE involves the need for high inspiratory pressure to counteract upper airway obstruction, subsequently causing a progressive rise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The primary etiology of NPPE is attributed to the generation of strong inspiratory negative pressure resulting from upper respiratory tract obstruction. 27 Following tracheal intubation and subsequent mechanical ventilation, resolution of the upper airway obstruction in our patient led to gradual resolution of the pulmonary edema ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 61%
“…The primary etiology of NPPE is attributed to the generation of strong inspiratory negative pressure resulting from upper respiratory tract obstruction. 27 Following tracheal intubation and subsequent mechanical ventilation, resolution of the upper airway obstruction in our patient led to gradual resolution of the pulmonary edema ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 61%
“…Usually the sign and symptoms of NPPE can be seen within 5 min but it can occur at any time after reliving of obstruction. In our case the symptom was seen with in 5 min as most cases but Koid.M and other researchers showed that there will be a probability of developing pulmonary oedema 1–6 h after upper airway obstruction 9 , 11 .…”
Section: Discussionmentioning
confidence: 95%
“…From the statistics of the Australian Incident Monitoring Study, the reported incidence rate of NPPE in patients with laryngospasm was 3% 8 . Thus, the incidence of NPPE can be ranged between 0.1 and 12% 9 . The incidence is higher in men (80%) and ASA physical states I and II (73%).…”
Section: Discussionmentioning
confidence: 99%
“…New treatments such as facedown positioning, inhaled nitric oxide, high-frequency breathing, surfactant therapy, and extracorporeal membrane oxygenation are currently being experimented with [ 16 ]. Research has been conducted on the use of bronchodilators in pulmonary edema, as studies suggest that bronchodilators, including β-agonists, could promote alveolar fluid clearance to lessen pulmonary edema symptoms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%